STUDY ON THE EFFECTIVENESS OF INORGANIC CORROSION INHIBITOR FOR MILD STEEL IN COOLING WATER SYSTEM - CHANG, YEE JIAN (IRC, 2017)
Corrosion of pipes in cooling systems is a serious problem in the industry which has led to the loss of pipeline integrity, increased maintenance cost and even unplanned shut down due to pipe leakage etc. With the rise of restrictions on the use of toxic chromate-based inhibitors in aqueous systems, industries have shifted their focus towards research on the less toxic soluble molybdate (MoO42–) and nitrite (NO2-) compound as an alternative corrosion inhibitor (CI) for steel. Therefore, this research aims to design and develop test jig for rotating cage test and mini flow loop test in order to determine the corrosion rate (CR) and effectiveness of CI for mild steel in different concentration under the influence of flow velocities of 0.3 m/s and 1.2 m/s, which are to simulate industries near stagnant condition and normal operating condition respectively. The final objective of this project is to analyze the microstructural surface of the corroded specimen to identify the corrosion behavior. Corrosion test by weight loss method using rotating cage and mini flow loop set up were carried out using simulated cooling water (SCW) as per ASTM G 170 and ASTM D 2688 respectively using mild steel sample AISI C1018. Steel specimens were machined and cut into strips then grinded and polished and later mounted to the rotating cage and mini flow loop rack for the corrosion test. For 1.2 m/s and 0.3 m/s flow velocity testing, the highest mean corrosion rates were 1.69 mmpy and 0.425 mmpy for uninhibited SCW respectively, whereas lowest mean corrosion rates were 0.006 mmpy and 0.005 mmpy for addition of molybdate and nitrite into SCW respectively. CI efficiency ranges from 93.5 – 99.7%. Higher flow velocity deemed to have more pitting on specimen surface for uninhibited SCW which could be caused by the disruption of the protective oxide film formation on the specimen. CR of mild steel in inhibited SCW was not impacted by higher flow velocity. Combination of molybdate and nitrite a corrosion inhibitor is the most efficient to mitigate corrosion for mild steel regardless of velocity.